CLIL in Higher Education: Impacts on Student Learning and Practical Implications. - Susilawati, Susilawati; Riniawati, Rina; Yunita, Sri; Darwis, Riadi (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2025)
Although Content and Language Integrated Learning (CLIL) has been increasingly implemented in Indonesian higher education, there is a need for a comprehensive understanding of its impact and effectiveness in university settings, highlighting the need for a systematic review to identify areas for improvement and inform recommendations for better practices. The present research aims to portray the effect of the implementation of CLIL on students' learning at the university level, as well as practical recommendations for CLIL learning in the future. A systematic literature review (SLR) was conducted to investigate CLIL implementation at the university level, covering both its impact on students' learning and future practical applications. This study reviewed 10 journal articles using the DISCAR design, sourced from the Sinta database and published between 2020 and 2025. The findings reveal that CLIL applied at the university level mostly affects students’ learning in the aspects of comprehension, learning motivation, 21st century skills, and collaborative work. Based on these findings, the study highlights recommendations for CLIL implementation, including developing balanced CLIL curricula and strengthening lecturers’ professional competence. Integrating CLIL into university learning is strongly recommended to equip students with balanced language competence, subject knowledge, and 21st-century skills, aligning with Indonesia's outcome-based education policy.